2014
DOI: 10.3354/meps10766
|View full text |Cite
|
Sign up to set email alerts
|

Localised mixing and heterogeneity in the plankton food web in a frontal region of the Sargasso Sea: implications for eel early life history?

Abstract: Previous studies have demonstrated that patches of eel larvae are found in the frontal region of the Subtropical Convergence Zone (STCZ), but to date no clear evidence of why this region might confer advantage to the larvae has been presented. This study demonstrates that there may be localized patches within a frontal region in the STCZ in the Sargasso Sea that experience elevated vertical mixing and an associated vertical flux of nutrients. This localized vertical mixing was suggested by a group of stations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…Richardson et al . () reported localized patches of highly elevated vertical mixing and associated nutrient enrichment of the euphotic zone in the same areas with high leptocephali abundances. This would probably stimulate the planktonic food web productivity and the presence of marine snow, which may be an important food source for leptocephali (Miyazaki et al ., ; Miller et al ., ).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Richardson et al . () reported localized patches of highly elevated vertical mixing and associated nutrient enrichment of the euphotic zone in the same areas with high leptocephali abundances. This would probably stimulate the planktonic food web productivity and the presence of marine snow, which may be an important food source for leptocephali (Miyazaki et al ., ; Miller et al ., ).…”
Section: Discussionmentioning
confidence: 90%
“…The prominent fronts in the STCZ study area were observed via satellite imagery and in situ hydrographic measurements (Munk et al, 2010). Average water depth at the eight stations was 5400 m. Hydrographic data were collected at each station with a SBE 9/11 CTD (Sea-Bird Electronic, Bellevue, WA, USA) prior to larval fish sampling and details on hydrographic characteristics have been reported elsewhere (Munk et al, 2010;Andersen et al, 2011;Riemann et al, 2011;Richardson et al, 2014).…”
Section: Study Area and Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all regions of the world's oceans where water column stratification occurs, the maximum chlorophyll concentration in the water column is often found well below the surface. In some cases, these deep chlorophyll maxima (DCMs) have been shown to contribute significantly to total water column PP (arctic: Richardson et al 2005, Martin et al 2013temperate: Weston et al 2005, Hickman et al 2012, Fernand et al 2013, Lyngsgaard et al 2014subtropical: Fawcett et al 2014, Richardson et al 2014. DCMs are often, but not always, positioned in or near the nutricline, and this has often been interpreted as the DCM being vertically positioned so that access to both light and nutrients is maximised (Klausmeier & Litchman 2001, Fennel & Boss 2003, Cullen 2015.…”
Section: Introductionmentioning
confidence: 99%